Private college students' knowledge, attitudes, practice, and associated factors towards the prevention of covid19 in Gondar town - Tarkie Abebe Walle; Yemataw Zewdu Temachu (Elsevier, 2023)
Background: The first cases of novel coronavirus (nCoV) were first detected in China and WHO declare a Public Health Emergency of International Concern on January two thousand twenty, and to characterize the outbreak as a pandemic on March two thousand twenty. Since then, COVID-19 is an emerging respiratory infection that was first discovered in Wuhan city, Hubei Province, China. Ethiopia is one of the countries which are affected by the pandemic. Therefore, we aimed to assess the status of private college students' knowledge, attitude, and practice about COVID-19 pandemic disease preventive measures in Gondar. Methods: Institution-based cross-sectional study was conducted among private college students. The study participants were recruited using a simple random sampling technique. Students from five Privet College from year one up to year four involved in this study. Data was collected using self-administered structured questioner with closed ended question. It includes four parts; the first section containing sociodemographic characteristics such as age, sex, educational status and category. The second part elicits about knowledge, the third part includes question concerning attitude and the last part includes practice associated factor questions towards prevention of coved 19. Data were analyzed using SPSS version 22 and presented via tables, figures, and in-text narration. The variables associated with the outcome were identified using multivariable logistic regression. Adjusted odds ratio with a 95 % confidence interval at p-value < 0.05 was fitted to declare the statistical significance. Results: A total of 384 private college students were enrolled in the study which makes a response rate of 100%. About 74.5% of college students had a good level of knowledge, 45.6% of college students had a good level of attitude, and 36.7% of college students had a good level of practice to prevent the COVID-19 pandemic. Marital status and year of study were statistically significant predictors of students' knowledge level, whereas none of the variables were statistically significant with attitude and practice of COVID-19 prevention. Conclusion: Private College students in Central Gondar town to have a good level of knowledge were as attitude and practice towards COVID-19 was less than half. Marital status and Year of the study were statistically significant predictors of students' knowledge level.